The use of driving impairing medicines, alcohol and other psychoactive substances in the population of professional drivers - Antonić, Roland; Pešić Ivanović, Milica; Jevtić, Danijela; Bogdanović Vasić, Slobodanka; Popović, Kosana; Beljić, Nikola; Damnjanović, Danijela; Janković, Slobodan; Folić, Marko (Archives of Pharmacy, 2022)
Medicines, alcohol and psychoactive substances have the potential to negatively affect driving ability, which increases the risk of traffic accidents, especially among professional drivers (1, 2). The aim of this research was to examine the use of driving impairing medicines, alcohol and psychoactive substances in the population of professional drivers. The research was conducted as a multicenter cross-sectional study in the Republic of Serbia and Bosnia and Herzegovina. The research population was consisted of 221 professional drivers, both genders, aged from 20 to 65, with a minimum of 2 years driving experience. Average age was 42.82 years. Driving impairing medicines were used by 9.95% of participants, while four of them used three or more of these medicines, most common anxiolytics (45.00%) and antidepressants (17.50%). Alcohol was consumed by 47.96% of respondents (32.08% often), while 53.39% of them were driving under the influence of alcohol. Psychoactive substances were used by 6.33% of respondents, of which twelve abused benzodiazepines, while one marijuana. Significantly lower levels of knowledge and attitudes of respondents about the impact of various psychoactive substances on the driving ability were confirmed among consumers of driving impairing medicines, alcohol and others (p<0.001). These results can be explained by inadequate penal policy and insufficient awareness of the respondents about the negative impact of psychoactive substances on the driving ability. The high prevalence of the use of driving impairing medicines, alcohol and psychoactive substances in the examined population was confirmed by this research, which can consequently pose a danger to traffic safety.